2023
DOI: 10.3390/molecules28031291
|View full text |Cite
|
Sign up to set email alerts
|

Method Validation for Multi-Pesticide Residue Determination in Chrysanthemum

Abstract: The chrysanthemum can be consumed in various forms, representing the “integration of medicine and food”. Quantitative analysis of multi-pesticide residues in chrysanthemum matrices is therefore crucial for both product-safety assurance and consumer-risk evaluation. In the present study, a simple and effective method was developed for simultaneously detecting 15 pesticides frequently used in chrysanthemum cultivation in three matrices, including fresh flowers, dry chrysanthemum tea, and infusions. The calibrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…To cope with these challenges, pesticides have been extensively used in the cultivation of chrysanthemum. 9 However, with the widespread application of pesticides, excessive exposure of pesticide residues has gradually become a major concern. 10 In a recent study, as many as 352 pesticide residues have been identified in edible chrysanthemum using gas chromatography tandem mass spectrometry (GC-MS), including organophosphorus pesticides fenthion, phoxim and isocarbophos.…”
Section: Introductionmentioning
confidence: 99%
“…To cope with these challenges, pesticides have been extensively used in the cultivation of chrysanthemum. 9 However, with the widespread application of pesticides, excessive exposure of pesticide residues has gradually become a major concern. 10 In a recent study, as many as 352 pesticide residues have been identified in edible chrysanthemum using gas chromatography tandem mass spectrometry (GC-MS), including organophosphorus pesticides fenthion, phoxim and isocarbophos.…”
Section: Introductionmentioning
confidence: 99%
“…It can be observed in many studies that magnetic element replacement of B cation surprisingly invokes multi‐ferroic and magneto‐electric effects in materials. For the last few decades, it has drawn the attention of researchers [4–7]. The structures like the perovskite family with transition metals (TMs) oxides reveals astonishing electronic characteristics for Mott insulators, metal insulators, and superconductors with extraordinary critical temperature due to increasing transportation in electrons of strongly coupled d‐states [8–11].…”
Section: Introductionmentioning
confidence: 99%